Epidemiology of Hepatitis B and C Viruses in the General Population of Dera Ismail Khan District (D.I. Khan) Pakistan - Din, Najm Ud; Saqib, Muhammad; Khan, Dawood; Perveen, Laila; Shah, Muhammad Kamal; Fareed, Muhammad; Khalil, Rubab; Hamid ur Rehman,; Khan, Amarat Ullah; Khan, Abdul Samad (Indus Journal of Bioscience Research, 2024)
Objective: This study aimed to determine the prevalence and epidemiology of hepatitis B (HBV) and hepatitis C (HCV) in the general population of Dera Ismail Khan, Pakistan, and to identify demographic and biochemical associations. Methods: A cross-sectional study was conducted involving 1,244 individuals randomly selected across various age groups and genders. Blood samples were collected and analyzed using immunochromatographic testing (ICT) and enzyme-linked immunosorbent assay (ELISA) to detect HBV surface antigen (HBsAg) and HCV-specific antibodies. Biochemical analysis of alanine transaminase (ALT) was performed using Microlab 300 (Merck, USA). Statistical analysis was conducted using SPSS version 25 to evaluate associations between demographic variables and disease prevalence. Results: The overall prevalence of HBV and HCV was 25.72%. HBV was detected in 228 (29%) individuals, with a higher prevalence in males (34.31%) compared to females (19.20%) and the 16-30 years age group (43.17%). HCV was identified in 92 (20.08%) individuals, with males (22.05%) more affected than females (17.43%), and the 46-60 years age group showing the highest prevalence (27.82%). ALT levels were significantly elevated in infected individuals, with mean values of 111.63 ± 101.38 in males and 143.50 ± 52.50 in females. Conclusion: The study highlights the substantial burden of HBV and HCV, emphasizing the need for enhanced public health interventions, including vaccination, early screening, and community education, to mitigate the disease burden.